Manufacturing Planning and Estimating Handbook / A Comprehensive Work on the Techniques for Analysing the Methods of Manufacturing a Product and Estmating Its Manufacturing Cost - Harvey Philip D; Wilson Frank W (Mcgraw Hill Book Company, 1963)
Preface, Manufacturing Analysis, Cost Estimating, Examples of Cost Estimates, Manufacturing Processing, Planning for Quality, Paperwork Systems, Methods Engineering, Planning for Tool Design, Plant Layout, Standards, Tolerance Charts, Linear Programming, Machine and Tookl Replacement Practices, Nomograms, Reference Tables.
Preface, Manufacturing Analysis, Cost Estimating, Examples of Cost Estimates, Manufacturing Processing, Planning for Quality, Paperwork Systems, Methods Engineering, Planning for Tool Design, Plant Layout, Standards, Tolerance Charts, Linear Programming, Machine and Tookl Replacement Practices, Nomograms, Reference Tables.